The TsuJal Amphibious Seismic Network: A Passive-Source Seismic Experiment in Western Mexico - Núñez-Cornú, Francisco Javier; Córdoba Barba, Diego; Bandy, William; Dañobeitia, Juan José; Alarcón Salazar, José Edgar; Núñez, Diana; Suárez Plascencia, Carlos (Frontiers in Earth Science, 2021)
The geodynamic complexity in the western Mexican margin is controlled by the multiple interactions between the Rivera, Pacific, Cocos, and North American plates, as evidenced by a high seismicity rate, most of whose hypocenters are poorly located. To mitigate this uncertainty with the aim of improving these hypocentral locations, we undertook the TsuJal Project, a passive seafloor seismic project conducted from April to November 2016. In addition to the Jalisco Seismic Network, ten LCHEAPO 2000 Ocean Bottom Seismometers (OBSs) were deployed by the BO El Puma in a seafloor array from the Islas Marías Archipelago (Nayarit) to the offshore contact between the states of Colima and Michoacan. We located 445 earthquakes in four or more OBSs within the deployed array. Most of these earthquakes occurred in the contact region of the Rivera, Pacific and Cocos plates, and a first analysis suggests the existence of three seismogenic zones (West, Center, and East) along the Rivera Transform fault that can be correlated with its morphological expression throughout the three seismogenic zones. The seismicity estimates that the Moho discontinuity is located at 10 km depth and supports earlier works regarding the West zone earthquake distribution. Subcrustal seismicity in the Central zone suggests that the Intra-Transform Spreading Basin domain is an ultra-low spreading ridge. A seismic swarm occurred during May and June 2016 between the eastern tip of the Paleo-Rivera Transform fault and the northern tip of the East Pacific Rise-Pacific Cocos Segment, illuminating some unidentified tectonic feature.